La généralisation du télétravail en Région de Bruxelles-Capitale - Claire Duchêne; Mathieu Strale; Marine Willeput; Nathan Pudles; Jean-Michel Decroly; Catherine Hellemans; Sabine Pohl; Magali Verdonck (Brussels Studies, 2024)
The Covid-19 crisis has had a deep impact on the way we work. For a few months, a large part of the Belgian population tried full-time teleworking, often for the first time. Seen initially as a way of limiting contact, teleworking has gradually taken root, becoming more common where it was already practised and extending to new positions and sectors not previously concerned. With this widespread implementation, major societal impacts are to be expected, particularly in Brussels, where teleworking is most widespread. It is important to anticipate them, to prepare for them and to adapt to them as best as possible. This article is part of a project to assess the social security debt associated with the widespread implementation of teleworking in Brussels by 2050. More specifically, based on recent literature and data, this article analyses the potential impact of teleworking in Brussels on well-being, the economy, employment, property, mobility and public finances.